Produção, caracterização nutricional e utilização de farinhas e óleos de resíduos de peixes neotropicais em dietas para Tilápia do Nilo - Higuchi, Leticia Hayashi [UNESP] (2015)
This work aimed to study neotropical fish processing waste for the production and characterization of meal and oil on an industrial scale, quantitatively and qualitatively, and to determine the nutritional value of the obtained meals. The experimental design was completely randomized (DIC) with two treatments and three replications on an industrial scale. The meal and oil were produced in Residue Processing Unit. The residues were cooked in the high temperature digester during 56 min and 129 min on average for patinga and pintado real flour, respectively. After processing, the fish meals' chemical composition and total amino acid profile were determined. Whereas, fish oils were characterized by the following indexes: peroxide, acidity, iodine, and fatty acid composition. The use of neotropical fish meals was evaluated by assessing the growth performance and body composition and hematological parameters, apparent digestibility coefficient, cost and economic efficiency of juvenile Nile tilapia. Four repetitions and four diets were tested: (patinga meal (FPA), pintado real® meal (FPR), marine fish meal (FPM) and poultry viscera meal (control) (FVA). A total of 320 juveniles (3.28 ± 0.47g) were distributed in 16 tanks (500L). The percentage yields for meals and oils were, respectively, on average: 22.97% and 25.08% for patinga (total 48.05%); and, 23.95% and 11.74% for pintado Real® (total 35.69%). The FPA had higher content of dry matter, ash, carbohydrates, energy, calcium and phosphorus, whereas the FPR had higher crude protein content. Among the essential amino acids, the FPR had higher isoleucine (4.16g/ 100g CP) and threonine (5.61g/100g CP) levels. Regarding non-essential amino acids, the FPR had higher cystine (0.45g/ 100g CP) while FPA had higher proline (7.46g/ 100g CP) contents. Total lipids, iodine index, cholesterol and peroxide did not differ between the oils. The FPR displayed higher digestibility of the protein ...